AMBIENT HYDROCARBON SPATIAL - TEMPORAL VARIATION ANALYSIS IN DKI JAKARTA AIR QUALITY MONITORING SYSTEM - Apta Ariowibowo, Dhiemas
DKI Jakarta as a big city with a high population density and varied population activities that affect the formation of air pollutants, one of them are hydrocarbon compounds. Hydrocarbons are classified into Total Hydrocarbons (THC) which is the total of Non-Methane Hydrocarbons (NMHC) and Methane Hydrocarbons (MHC). Landuse differences at each monitoring location, number of vehicles, and hydrocarbon involvement in photochemical reactions leads to hydrocarbon concentration temporal and spatial variations. This study aims to perform spatial temporal analysis of hydrocarbon compounds and analyze the correlation of hydrocarbon and NOx, NO, NO2, O3, BTEX compounds. Based on available observational data in 2018 – 2019, it is known that there are seasonal and annual temporal variations, as well as spatial variations shows that the highest hydrocarbon concentration found in DKI 1 (Bundaran HI, Central Jakarta), then DKI 5 (Kebon Jeruk, West Jakarta), and finally DKI 3 (Jagakarsa, South Jakarta). The results of the correlation test in DKI 1 and DKI 5 shows a directly proportional with NOx, NO2, NO, and O3 compounds, while in DKI 3 it was the other way around. In addition, the correlation results in DKI 1 and DKI 5 shows an inversely proportional to BTEX compounds, while in DKI 3 shows directly proportional.